Use of Geo-Informatics in Flood Hazard Mapping: A Case of Balkhu River - Dangol, Susheel (Journal on Geoinformatics, Nepal, 2017)
Flood is one of the striking water induced disaster that hits most of the part of the world. In Nepal also it is one of the serious disasters which affect the study describes the technical approach of probable flood hazard analysis. Segment of Balkhu River within the Balkhu catchment of area 44.37 km2 from Kirtipur gorge to Bagmati confluence was taken as area of study. The total length of the study segment was 5485.89 m. One dimension HEC-RAS (Hydrologic Engineering Center-River Analysis System) model was used for the analysis. The study shows that higher flood depth increases and low flood depth decreases with increase in intensity of flood. Also, huge area of barren land area is affected by flood and few percentage of settlement area is affected by flood indicating the damages to the human lives. Huge area of barren land indicates that in future human lives are more prone to disasters as those lands have gone through planning for future settlement. Nepalese Journal on Geoinformatics -13, 2014, Page: 52-57